Rifapentine is an entry and replication inhibitor against yellow fever virus both in vitro and in vivo. Issue 1 (31st December 2022) - Qian, Xijing; Wu, Bingan; Tang, Hailin; Luo, Zhenghan; Xu, Zhenghao; Ouyang, Songying; Li, Xiangliang; Xie, Jianfeng; Yi, Zhigang; Leng, Qibin; Liu, Yan; Qi, Zhongtian; et al.
ABSTRACT: Yellow fever virus (YFV) infection is a major public concern that threatens a large population in South America and Africa. No specific anti-YFV drugs are available till now. Here, we report that rifapentine is a potent YFV inhibitor in various cell lines by high-throughput drugs screening, acting at both cell entry and replication steps. Kinetic test and binding assay suggest that rifapentine interferes the viral attachment to the target cells. The application of YFV replicon and surface plasmon resonance assay indicates that rifapentine suppresses viral replication by binding to the RNA-dependent RNA polymerase (RdRp) domain of viral nonstructural protein NS5. Further molecular docking suggests that it might interact with the active centre of RdRp. Rifapentine significantly improves the survival rate, alleviates clinical signs, and reduces virus load and injury in targeted organs both in YFV-infected type I interferon receptor knockout A129 −/− and wild-type C57 mice. The antiviral effect in vivo is robust during both prophylactic intervention and therapeutic treatment, and the activity is superior to sofosbuvir, a previously reported YFV inhibitor in mice. Our data show that rifapentine may serve as an effective anti-YFV agent, providing promising prospects in the development of YFV pharmacotherapy.